2003
DOI: 10.1097/00004836-200311000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Transradial Approach for Transcatheter Arterial Chemoembolization in Patients With Hepatocellular Carcinoma

Abstract: We evaluated the clinical usefulness and safety of transradial approach for transcatheter arterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC) compared with that of conventional transfemoral approach. The two groups (radial group, n = 177; femoral group, n = 150) of cases were retrospectively compared with regard to the successful rate of angiography or TACE, time required for catheterizaiton and complications. Hepatic angiography and TACE were completed in 174 (98.3%) of 177 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…According to our knowledge, there are only a few hospitals where radial access is regularly performed for interventions in the systemic circulation. Most of the related publications report the use of radial access for cerebral angiograms and carotid artery stenting (16,17) and only a few report procedures below the diaphragm (11)(12)(13)(14)(15). Only three groups reported abdominal or pelvic visceral interventions in the English literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our knowledge, there are only a few hospitals where radial access is regularly performed for interventions in the systemic circulation. Most of the related publications report the use of radial access for cerebral angiograms and carotid artery stenting (16,17) and only a few report procedures below the diaphragm (11)(12)(13)(14)(15). Only three groups reported abdominal or pelvic visceral interventions in the English literature.…”
Section: Discussionmentioning
confidence: 99%
“…Only three groups reported abdominal or pelvic visceral interventions in the English literature. A group at Tokyo Women's Medical University Daini Hospital (Tokyo, Japan) reported that they performed abdominal interventions in 426 patients between 2000 and 2004 via the transradial approach, including 177 cases of transarterial hepatic chemoemboli-zations (15,22); Ruzsa et al (14) reported renal artery angioplasty and stenting in 27 patients; Resnick et al (13) reported uterine artery embolization in 29 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported 16,17 , a 4-Fr catheter was inserted into the left radial artery, and super selective embolization was performed on the tumor with staining on hepatic arteriography concurrently using a microcatheter in the TACE procedure. Miriplatin (miriplatin hydrate, Sumitomo Dainippon Pharma Co., Ltd, Osaka, Japan) 40 to 80 mg/body and iodized oil (Lipiodol; Lipiodol Ultrafluide, Laboratoire Guerbet, Aulnay-sous-Bois, France) were mixed at an equal ratio and injected during the embolization according to the diameter and number of tumors.…”
Section: Procedures Of Tacementioning
confidence: 99%
“…In 2003, TACE using TRA was first described in Japan. 18 Shiozawa et al retrospectively compared 150 TACE patients who underwent TFA and 177 patients who underwent TRA. Of the 70 patients who received both approaches, 92.9% preferred TRA.…”
Section: Catheter Selectionmentioning
confidence: 99%